How Stressful Is Examining Children with Symptoms of Child Abuse?-Measurement of Stress Appraisal (SAM) in German Physicians with Key Expertise in Pediatrics - Louisa Thiekötter; Peter Schmidt; Marie-Léne Scheiderer; Heidrun Lioba Wunram; Michael Paulussen; Daniela Reis; Oliver Fricke (MDPI AG, 2022)
Background: Pediatricians frequently feel uncertain about their ability to detect early symptoms of child abuse and how to respond in suspected cases. Aim: This study investigated the transactional stress model in German pediatricians who experienced imagination stories with a child protection scenario and another potentially stress-triggering scenario. Methods: A two-part survey was conducted online. Each part included a different imagination story and evaluation of the Stress Appraisal Measure (SAM), as well as questions on child protection, current problematics, and suggested remedies. In total, 96 pediatricians participated. The child abuse scenario was perceived as significantly more threatening and more stressful than a medical emergency. The pediatricians declared moderate familiarity with the Child Protection Guidelines and the Federal Child Protection Act and an average confidence in their application. The greatest perceived problems were communication difficulties with parents and youth welfare services. Suggested improvements were concrete procedural directives, more training programs, better interdisciplinary networks, and greater exchange among colleagues. Conclusions: To optimize their potential in the child protection system, pediatricians need to be better supported in coping with the identified stressors in child abuse scenarios.